2012
DOI: 10.1016/j.jsb.2011.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the amino-acid sequence and the 3D structure of the functional domain of EmaA from Aggregatibacter actinomycetemcomitans

Abstract: Adhesion to collagen is an important virulence determinant for the periodontal pathogen Aggregatibacter actinomycetemcomitans. Binding to collagen is mediated by the extracellular-matrix protein adhesin-A (EmaA). EmaA is a homotrimeric autotransporter protein that forms flexible antenna-like appendages on the bacterium surface. An ellipsoidal structure at the distal end of the appendage, composed of 3 subdomains, contains the functional domain of the molecule. A correlation between amino-acid sequence and subd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 38 publications
(67 reference statements)
1
43
0
Order By: Relevance
“…EmaA molecules assemble into antenna-like appendages on the surface of the bacterium and specifically bind to collagen (16,25,32). It has also been proposed that collagen interacts with the head domain of EmaA, which correspond to the N termini of the proteins, or the globular ends of the antenna-like cell surface appendages (1,36). The EmaA structures, which extend at least 150 nm from the surface, have been implicated in the initiation of infective endocarditis (31).…”
mentioning
confidence: 99%
“…EmaA molecules assemble into antenna-like appendages on the surface of the bacterium and specifically bind to collagen (16,25,32). It has also been proposed that collagen interacts with the head domain of EmaA, which correspond to the N termini of the proteins, or the globular ends of the antenna-like cell surface appendages (1,36). The EmaA structures, which extend at least 150 nm from the surface, have been implicated in the initiation of infective endocarditis (31).…”
mentioning
confidence: 99%
“…1D). Images of the wild-type strain show grooves on the bacterial surface and also the presence of the collagen binding adhesin, extracellular matrix adhesin A (EmaA), that forms antenna-like structures protruding from the bacterial surface (13,22,30,31). Our earlier studies revealed that convolutions in A. actinomycetemcomitans are associated with a protein called morphogenesis protein C (MorC), which appears to be located in the inner membrane (29).…”
Section: Resultsmentioning
confidence: 99%
“…However, the loss of the rugosity does not seem to influence the presentation of all virulence determinants on the outer bacterial surface. EmaA (extracellular matrix adhesin A), a trimeric autotransporter collagen binding adhesin that forms antenna-like appendages on the surface of the bacterium (13,22,30,31), is present in both wild-type and morC mutant strains, thus indicating that not all outer membrane transport systems are affected. All of these observations raise fundamental questions about the specific role of the outer membrane morphology and the spatial relationship between outer and inner membranes in bacteria with a native rugose phenotype.…”
mentioning
confidence: 99%
“…EmaA adhesins from a serotype b strain were analyzed by electron tomography of whole-mount negatively-stained preparations of the bacteria (Fig 2.a) [3]. Tomographic single-axis tilt series over a ±64° angular range in 2° intervals were acquired with a calibrated pixelsize at the specimen scale of 0.308 nm.…”
mentioning
confidence: 99%